Development and prospect of mobile gravity monitoring and earthquake forecasting in recent ten years in China - Yiqing Zhu; Fang Liu; Guoqing Zhang; Yunma Xu (Geodesy and Geodynamics, 2019)
After the Wenchuan earthquake in 2008, China Earthquake Administration has strengthened the monitoring of mobile gravity and earthquake forecasting. This paper mainly analyzes the development of mobile gravity monitoring network of China in 2008, the role of time-varying gravity field in the determination of strong earthquake risk and the technical problems that gravity monitoring still needs to be solved. By analysing the mobile gravity monitoring and earthquake prediction in China, the characteristics of gravity anomaly and three elements of earthquake prediction are discussed. The mobile gravity observation data can better reflect the gravity anomalies before the earthquake, especially the strong earthquakes greater than Ms6.0. Finally, we put forward the reconsideration of the development strategy of mobile gravity monitoring and earthquake forecasting in China. Keywords: Mobile gravity monitoring, Wenchuan earthquake, Lushan earthquake, Earthquake prediction